This might be sort of an embarrassing question but I was reviewing real analysis and its quite common to have to use inequalities and upper/lower bounds there. So I was wondering if there was a clear set of rules of how to upper bound things?

For example, I was in particular considering:

$$ b^n - a^n = (b-a)(a^{n-1} + a^{n-2} b + \cdots + ab^{n-2} + b^{n-1})$$

and wanted to place inequalities bounds on it. When $b>a \iff b-a > 0$ then it seems that we can simply place the inequality:

$$ b^n - a^n = (b-a)(a^{n-1} + a^{n-2} b + \cdots + ab^{n-2} + b^{n-1}) < (b-a)nb^{n-1}$$

regardless of the sign of $b$ and $a$ (which seems to matter in my next example/case).

however, when $b < a \iff b-a < 0$ it seems the situation is different and I was wondering if it was something in particular to just this example of a general rule for placing upper and lower bounds that I am unaware of. In this case $b < a \iff b-a < 0 \implies b^n < a^n \iff b^n - a^n < 0$. Thus we get that on the LHS we have something negative and on the RHS we one negative term ($b-a$) multiplied by $(a^{n-1} + a^{n-2} b + \cdots + ab^{n-2} + b^{n-1})$ with an unknown sign as of yet. But since $a>b$ we do know one thing that $(a^{n-1} + a^{n-2} b + \cdots + ab^{n-2} + b^{n-1}) < n a^{n-1}$. Intuitively it means the second term increases. Thus, at least intuitively it seems to me that if I try to substitute the above inequality if $n a^{n-1} > 0$ is positive, then we actually get a lower bound (since we have something negative with something that increased being multiplied by it) i.e.

$$ b^n - a^n = (b-a)(a^{n-1} + a^{n-2} b + \cdots + ab^{n-2} + b^{n-1}) > (b-a)n a^{n-1} $$

however, this seems rather subtle and it seems this case does not happen for some reason during the first inequality I showed. What is the reason? In particular, I am interested in understanding if it just means in general I always have to be really careful when I try to bound things (since it seems inequalities my change rather subtly if one is not careful) or is there a general principle that I am missing? Or is it just case by case? Or is there something funky in this particular example due to multiplication?

In this special case it seems the inequality switches sign whenever $n$ is odd or even if $a < 0$, since for even n $ a^n >0 $ and for odd $a^n < 0$ so depending which one we have we have a different inequality. Is this true?


The basic principle is: if $A \le B$ and $c \ge 0$, then $Ac \le Bc$. If $A \le B$ and $c \le 0$, then $Ac \ge Bc$.

In the case at hand, consider $$a^n - b^n = (a-b) (a^{n-1} + a^{n-2} b + \ldots + b^{n-1})$$

I think you want to assume $a > 0$ and $b > 0$. Then if $a > b$ you have $a^{n-1} \ge a^{n-j} b^j \ge b^{n-1}$ for all $j$ from $0$ to $n-1$, so

$$ n a^{n-1} \ge a^{n-1} + a^{n-2} b + \ldots + b^{n-1} \ge n b^{n-1}$$

and multiplying by $a - b > 0$ you get

$$ n a^{n-1} (a-b) \ge a^n - b^n \ge n b^{n-1} (a-b) $$

If $a < b$ you get the same thing with $a$ and $b$ interchanged, so in this case

$$ n b^{n-1} (b-a) \ge b^n - a^n \ge n a^{n-1} (b-a) $$

or, multiplying by $-1$, to get:

$$ n b^{n-1} (a-b) \le a^n - b^n \le n a^{n-1} (a-b) $$

| cite | improve this answer | |
  • $\begingroup$ weird, do you have a typo on your 3rd line? $\endgroup$ – Pinocchio Jun 9 '17 at 3:24

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.